Perceived Risk and Trust as Moderators Between Online Shopping Intention and Purchase Decisions - Tu Ngoc Tran; Le Dinh Nghi; Dinh Thi Kieu Chinh (Ital Publication, 2026)
This study aims to identify the factors influencing online shopping intention and purchase decisions among consumers in Ho Chi Minh City, while examining the moderating roles of perceived risk and trust in e-commerce. Data were collected through a structured survey of online shoppers and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The empirical results indicate that product quality, price, promotion programs, and website quality have significant positive effects on online shopping intention, which in turn exerts a strong influence on purchase decisions. Moreover, perceived risk negatively moderates, whereas trust in e-commerce positively moderates the relationship between online shopping intention and purchase decisions. These findings underscore the pivotal roles of perceived value, trust formation, and risk reduction in converting online shopping intention into actual purchasing behavior. The novelty of this study lies in simultaneously examining perceived risk and trust as moderating mechanisms within a PLS-SEM framework in an emerging market context. The results provide practical insights for e-commerce firms by highlighting the importance of improving website quality, enhancing security systems, adopting flexible pricing strategies, and designing targeted promotions to increase online shopping conversion rates.